Expression, purification and preliminary crystallographic studies of the C‐terminal SH3 domain of human Tks4. Issue 3 (1st March 2014) - Huang, Yuxin; Qian, Huolian; Wang, Xiaoying; Cheng, Zhong; Ren, Jixia; Zhao, Weichen; Xie, Yong
<x xml:space="preserve">Abstract</x> The Src homology 3 (SH3) domain is a small, noncatalytic domain with a conserved sequence of about 60 amino‐acid residues that interacts with proline‐rich peptides to form a protein complex. In this study, the C‐terminal SH3 domain of human Tks4 (residues 853–911) was expressed, purified and crystallized. X‐ray diffraction data were collected to 2.3 Å resolution. The crystal belonged to the trigonal space group P3121 (or P3221), with unit‐cell parameters a = b = 83.87, c = 108.44 Å, α = β = 90, γ = 120°. Calculating the self‐rotation and the native Patterson function did not lead to the detection of any noncrystallographic translational symmetry. Six, seven or eight protein molecules are likely to be present in the asymmetric unit, resulting in a Matthews coefficient and approximate solvent content of 2.71 Å3 Da−1 and 55%, 2.32 Å3 Da−1 and 47%, and 2.03 Å3 Da−1 and 39%, respectively. To solve the crystal structure of the C‐terminal SH3 domain of human Tks4, the isomorphous replacement method is presently being utilized.